Value Clarification Technique as a Character Education Strategy in Social Studies Learning for Elementary School Students - Rahmanda, Rasnida; Zakiah, Linda; Sumantri, Syarif (BASICA, 2025)
The complexity of contemporary social challenges demands character education that not only transmits values but also deeply internalizes moral values in elementary school students, particularly through Social Studies (IPS) learning. This study aims to analyze the effectiveness of the Value Clarification Technique (VCT) in strengthening moral knowing and tolerance attitudes, map variations in implementation practices, and identify factors influencing its successful application. The method employed is a systematic literature review (SLR) using the PRISMA protocol, with primary research articles sourced from Scopus, Web of Science, ERIC, ScienceDirect, Google Scholar, and Portal Garuda databases for the period 2021–2025. Twenty articles meeting the inclusion criteria were thematically analyzed. The results show that VCT consistently and significantly enhances students' moral reasoning, tolerance, empathy, and responsibility through a structured value reflection mechanism. Implementation variations include integration with innovative media (such as Pop Up Books, puzzles), project-based assessments, and structured philosophical dialogues. The success of VCT implementation is influenced by teachers’ pedagogical competence, students’ initial moral readiness, family environment support, duration of exposure, and the quality of presented moral dilemmas. Practical implications emphasize the importance of teacher training and VCT integration in character education curricula. This study affirms VCT as a holistic and adaptive approach to strengthening elementary students’ character, while recommending further experimental and longitudinal research to examine its long-term impact.